The reading interests and habits of Science curriculum students and Science high school students in Quezon City - Guzman, Jamie G.; Dorado, Dan Anthony D. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2014)
The reading interests and habits of a person can be affected by numerous factors. On this study, the socio-economic status, the extra-curricular and personal activities and the mass media are among of those many which are tested if they are contributory to the reading interests and habits of the science curriculum students and science high school students in Quezon City.
The researcher conducted two types of surveys. First was a pre-survey which was designed to be all open-ended and second was the final survey questionnaire composed of 30 multiple choice type questions. The survey questionnaires were given to three schools namely Philippine Science High School, Quezon City High School, and Ramon Magsaysay High School. A total of 60 respondents participated for the pre-survey and 240 respondents for the final survey.
The Pearson's Correlation Coefficient was used to correlate the time spent reading by the students and the different assumed factors such as the socio-economic level of the student, extra-curricular and personal activities done by the student and the mass media consumed by the student's.
The data gathered from the survey questionnaires revealed that: (a) the income of the parents of the students is correlated with the time the student spend on reading; (b) the extra-curricular activities participated by the students do not correlate to the time the students spend on reading; (c) the mass media consumption of the students do not correlate to the time the students spend on reading and (d) the personal activities of the students do not correlate to the time the students spend on reading.
Undergraduate thesis(B.L.I.S.)--University of the Philippines, Diliman
Keywords: Reading interests -- Philippines -- Quezon City; High school students -- Philippines -- Quezon City